HUBUNGAN DURASI PENGGUNAAN KONTRASEPSI ORAL DENGAN TEKANAN DARAH AKSEPTOR KONTRASEPSI DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA PEKANBARU TAHUN 2020 - Ratih Ayuningtiyas; Sinta Rahmah Sari (STIKes Al-Insyirah Pekanbaru, 2021)
Each year, 63% of all deaths in the world is caused by non-communicable diseases (NCDs), including coronary heart disease hypertension. Based on the cause, hypertension is divided into two types, i.e. primary or essential hypertension, whereas one of the causes is a genetic factor, and secondary hypertension, whereas one of the causes is the use of oral contraception. Family planning participants who actively use oral contraception or pills in Pekanbaru reached 45,600 people. Determine of this study was the correlation between duration of oral contraception or pill use and blood pressure in contraception acceptors within the working area of Harapan Raya Community Health Center, Bukit Raya, Pekanbaru. The type of this study was analytical observation with a cross-sectional approach. Samples were obtained by stratified random sampling. Spearman test results showed that the correlation coefficient of systolic blood pressure was 0.310 with a p-value of 0.000 (p < 0.01), and diastolic blood pressure was 0.298 with a p-value of 0.000 (p < 0.01). There was a correlation between the use of oral contraception or pills and systolic or diastolic blood pressure in contraception acceptors. Keywords: blood pressure, duration, oral contraception or pills